Call to Action for Enhanced Equity: Racial/Ethnic Diversity and Sex Differences in Stroke Symptoms - Hosman, Floortje L.; Engels, Sabine; den Ruijter, Hester M.; Exalto, Lieza G. (Frontiers in Cardiovascular Medicine, 2022)
Background: Fundamental aspects of human identity may play a role in the presentation of stroke symptoms and, consequently, stroke recognition. Strokes must be recognized and treated expeditiously, as delays result in poorer outcomes. It is known that sex plays a role in the presentation of symptoms, such that non-traditional symptoms are more commonly observed among women. However, other factors, such as geographical location and race/ethnicity, and the interaction between these various factors, need to be considered, providing an intersectional approach. Methods: A systematic review and meta-analysis of the literature was conducted to investigate differences in the presentation of stroke symptoms between sexes. Using PubMed and Embase, a search involving the components sex, symptoms and stroke was completed and yielded 26 full-text manuscripts. Results: Our findings indicate that there is substantial overlap in stroke symptom presentation in men and women. Nonetheless, some differences in the clinical manifestations of stroke were observed. In addition, it was discovered that only three studies were conducted outside of North America and Europe. Furthermore, only two studies reported symptoms based on both sex and racial/ethnic group. Conclusion: These findings indicate a research gap and call for increased research in order to uncover the possible interactions between sex and race/ethnicity in an intersectional approach. Resultantly, stroke recognition could be improved and greater equity in healthcare can be achieved.